A Review and Analysis of the Effects of Financial Slack on Firm Innovation - (:unkn) unknown (My University, 2013)
I analyze the effect of financial slack on firm innovation by reviewing prior research and conducting an empirical analysis. The goal of this paper is to describe, refine and expand research on the relationship between financial slack and innovation. I describe how past scholars' conceptualizations and operationalizations of financial slack vary across studies and are often inconsistent with theoretical definitions suggesting that financial slack is a resource that exists in excess of some foreseeable need. My theoretical analysis suggests that one solution to this problem may be to operationalize financial slack as a proportion of total R&D spending (what I refer to as the financial slack-R&D ratio). Research suggests that innovation outcomes may be more strongly affected by the ratio of financial slack relative to total R&D spending than by financial slack measured independent of R&D spending. However, few, if any scholars have operationalized financial slack as a proportion of total R&D spending. I assess the moderating role of project and department level variables that are easily observable (readily accessible to firm managers), universal (found across firms and across industries) and for which the management literature provides conflicting support regarding their likely influence on the financial slack-innovation relationship. Specifically, I explore the influence of portfolio effects (the number and diversity of R&D projects) and maturity effects (nearness to completion) on the amount of financial slack-R&D ratio needed to optimize innovation outcomes. I test my hypotheses using data from a sample of U.S.-based biotechnology firms attempting to develop new pharmaceutical drugs.
Keywords: Financial Slack; Firm Innovation; Portfolio Theory